Pediatric appendicitis- five year experience at tertiary care pediatric surgery department: a cohort study - Albal, Manisha; Bansod, Prasad Y.; Mashru, Deep (International Surgery Journal, 2020)
Background: Acute appendicitis is one of the most common abdominal surgical condition in pediatric population. It accounts for 1-8% of children presenting in pediatric surgical emergency. The aim of this study was to evaluate pediatric appendectomy in our department. Methods: It was a hospital based prospective cohort study spanning over a period of 5 years, where all diagnosed cases of pediatric appendicitis were enrolled. Demographic profile, clinical features and operative findings were analyzed. Patients were kept on regular follow-up and complications were noted. Results: During the study period 146 patients were enrolled for the study. Male: female ratio was 1:1. Maximum patients belonged to age group of 11-15 years (42%). Pain in abdomen and fever were the most common presenting symptoms. Tenderness in right iliac fossa was the most common clinical sign (89.72%) and inflamed appendix was the most common operative finding in the study (83.91%). Conclusions: The diagnosis of acute appendicitis is based on clinical examination. Atypical symptoms may lead to delay in the diagnosis and management. Imaging and lab investigations are supportive. Early recognition of symptoms, access to healthcare facility with a surgeon can significantly reduce the morbidity and complication rates in pediatric age group.